The Influence Of Financial Performance, Audit Quality, Earnings Management On Tax Avoidance With Capital Intensity As A Moderating Variable - Yosua Manullang (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze and provide empirical evidence on the influence of profitability on tax avoidance; the influence of leverage on tax avoidance; the influence of audit quality and earnings management on tax avoidance; the moderation effect of capital intensity on the relationship between profitability and tax avoidance; the moderation effect of capital intensity on the relationship between leverage and tax avoidance; and the moderation effect of capital intensity on the relationship between audit quality and earnings management with tax avoidance. The research methodology employed is quantitative. Secondary data sources consist of financial reports from companies in the infrastructure sector listed on the Indonesia Stock Exchange during the period 2020-2022. The population comprises companies in the infrastructure sector, with a sample size of 111 selected using purposive sampling based on specified criteria. The research employs panel data regression analysis, with data processed using Eviews version 12. Partially, the study finds that ROA, leverage, and audit quality significantly influence tax avoidance, while earnings management does not significantly affect tax avoidance. Capital intensity strengthens the influence of ROA and earnings management on tax avoidance, while weakening the influence of leverage and audit quality on tax avoidance.